THE SPECIAL FEATURES OF FUTURE CIVIL ENGINEERS’ TRAINING FOR ENGINEERING ACTIVITY - Пришупа, Юлия; Конопляник, Леся (SWorldJournal, 2020)
The paper considers the peculiarity of engineering activity and its orientation to solving social and technical tasks. The authors analyse the required skills and traits for civil engineers set by Ukrainian and foreign employers and special organizations